Enhancing Civil Engineering teaching through 3D Computer Aided Design - Gonçalves, Jorge (2020)
3D interpretation of 2D drawing is not easy for most of the Civil Engineering first-year students. Some do it naturally but most need to be trained to master this skill. In this paper, the implemented teaching methodologies aiming to facilitate the acquisition of three-dimensional project visualization skills are presented. These methodologies were developed during the last two years targeting first-year Civil Engineering students at the University of Beira Interior (Portugal). After a first contact with 2D project representation through manual drawing, students progressively elaborate computer-aided design (CAD) project starting with simple 2D drawings and culminating with a 3D project of a pre-existing building. Students are also motivated to improve their 3D graphic representation skills through a classroom contest where the winning project is printed in 3D. The training in 2D and 3D graphic representation is complemented during the second year with several in situ surveys and computer-aided drawing of topographic data. This approach proved to be very interesting for competence acquisition, qualifying students for a better 3D representation and interpretation. Students also found this methodology to be motivating.